Spin-dependent magnetism and superparamagnetic contribution to the magnetocaloric effect of non-stoichiometric manganite nanoparticles. (March 2022) - Liedienov, Nikita A.; Wei, Ziyu; Kalita, Viktor M.; Pashchenko, Aleksey V.; Li, Quanjun; Fesych, Igor V.; Turchenko, Vitaliy A.; Hou, Changmin; Wei, Xu; Liu, Bingbing; Kozakov, Aleksey T.; Levchenko, Georgiy G.
Highlights: La0.8- x □ x Na0.2 Mn1+ x O3-Δ with strong spin-electron coupling has been prepared. Well-developed crystalline spherical-like nanoparticles contain Mn B 3+, Mn B 4+, Mn A 2+ . Spin-dependent magnetism is observed due to e g -electron localization–delocalization. Multicomponent nonlinear magnetic system shows complex critical behaviour near T C . Superparamagnetic contribution of nanoparticles to magnetocaloric effect was found. Abstract: Despite extensive research on manganites owing to their potential use in modern technologies, some aspects of their behaviour associated with changes in spin, valence, and charge states remain unclear. In this work, we investigated the structural, magneto-transport, and magnetocaloric properties of La0.8- x □ x Na0.2 Mn1+ x O3-Δ manganite nanoparticles with strong spin-electron coupling. It was found that the perovskite structure contained different valence manganese ions, Mn B 3+, Mn B 4+, and Mn A 2+, even in the pristine compound. With an increase in x, increases in the Curie temperature T C, spontaneous magnetization, and magnetic entropy change Δ S M, as well as a decrease in the metal-semiconducting temperature T ms, were detected. The change in the spin value of Mn ions during the transition from ferromagnetic-metallic ( μ FM exp < μ FM theor ) to the paramagnetic-semiconducting ( μ PM exp > μ PM theor ) state owing to the localization–delocalization process of e g -electrons on the Mn sites was found to indicate spin-dependent magnetism. The complex critical behaviour is manifested near T C with a second-order phase transition. An additional influence of the super-paramagnetism of nanoparticles on the magnetocaloric effect was determined. Graphical abstract: Image, graphical abstract .